Level of understanding towards Wadiah Contract among Muamalat students in UiTM Puncak Alam / Sumayyah Abdul Somat - Abdul Somat, Sumayyah (2019)
Wadiah contract is one of Islamic banking products. Whereareas a lot of people still lack of knowledge about Islamic banking products. Some people also misunderstood on concept of Wadiah Yad Dhamanah where they thought that Wadiah profit gain process like an investment profit gain but those two is so different in process. Besides, acceptance of Wadiah contract as deposit contract were not too wide in Malaysia society. It is important for the research to be done in solving these problems. The aim of this research is to study level of knowledge on Wadiah contract among Muamalat students in UiTM Puncak Alam. This research is using quantitative methodology which obtained data from a survey questionnaire that been distributed. The data was analysed by Statistical Package for Social Science (SPSS) version 20 which is a Windows-based program that can be used to generate tables and graphs to perform data entry and analysis. The research result show that most of student have a high understanding and know about Wadiah contract because they have already learned in the lecture. At the same time, a few of student still mistaken on some of element in Wadiah contract. Hope all student can understand and study about Wadiah contract thoroughly, so they can apply Wadiah contract in their financial affair in future.